Modifikasi Latihan Passing dengan Sasaran Tetap dan Berpindah pada Kaki Terlemah untuk Meningkatkan Ketepatan Passing Sepak Bola - Saputra, Taufan Fandi; Humaid, Hidayat (Jurnal Kepelatihan Olahraga, 2024)
This research aims to compare the effect of fixed target and moving target passing exercises on the weakest foot on passing accuracy on the Jakarta State University football header using an experimental method with a Matched Subject Design namely an experiment that uses two sample groups that have been compared subject by subject before the treatment is carried out. The sample used in this research was 24 students at Jakarta State University using a purposive sampling technique. Data collection techniques before and after carrying out passing activities are then processed and analyzed using SPSS. The results of the t test shows 1) there is a significant effect of fixed target passing practice on passing accuracy 2) there is a significant effect of moving target passing practice on passing accuracy and 3) there is no difference between fixed and moving target passing practice on passing accuracy.